Lessons Learned from the First 10 Years of the Oaks and Prairies Joint Venture’s Grassland Restoration Incentive Program (GRIP) - James J. Giocomo; Robert M. Perez; Kenneth Gee; Steven Riley; Derek Wiley; Anna M. Matthews; Ty Higginbotham; Amanda Haverland; Thomas S. Janke; Amber Brown; Kati Biggs; Mitchell Riggs; et al. (National Quail Symposium Proceedings, 2022)
The Oaks and Prairies Joint Venture (OPJV) was formed in 2008 as a public-private partnership of agencies and organizations working across jurisdictional boundaries in portions of Texas and Oklahoma, USA. The OPJV’s major focus is reversing declines of bird populations by supporting strategic habitat conservation (biological planning, conservation design, conservation delivery, mission-based monitoring, and assumption-driven research) for northern bobwhite (Colinus virginianus), grasslandobligate species, and their respective habitats. Our objective for this paper is to document and share a decade of lessons learned in developing a partnership-based native grassland conservation program to meet grassland bird conservation targets. We share lessons learned about how to manage partnership-based, large-scale habitat incentive programs to better target project locations and habitat practice types. To establish initial shared purpose, OPJV partners drew from population and habitat objectives in various state, national, and international bird conservation plans, stepped down to ecoregion levels, to establish the OPJV Grassland Bird Conservation Business Plan. The plan has 4 strategies directly contributing to the achievement of OPJV grassland bird biological objectives that are directly supported by OPJV staff or resources (or both). The overall objective for 2015–2025 was 619,978 ha (1,532,000 acres) improved within 40 focal counties, representing 1/3 of all counties in the OPJV. Our main strategy was to provide financial incentives through the OPJV Grassland Restoration Incentive Program (GRIP) to private landowners for conducting beneficial grassland bird habitat management practices. Since inception in 2013, GRIP has treated over 44,515 ha (110,000 acres) on private lands in Texas and Oklahoma, with the goal of maintaining highquality grassland bird habitat on treated hectares for ≥5 years. In 2017, OPJV partners working with USDA Natural Resources Conservation Service, began a 5-year, 6.1 million partnership to provide additional technical and financial assistance to private landowners interested in grassland conservation through the Regional Conservation Partnership Program (RCPP). A project scoring system was designed to strategically encourage individual projects to include prescribed fire—one of the lowest cost practices per hectare—as a recurring practice to maintain program-achieved grassland improvements. Post-inception of the RCPP, the area treated with prescribed fire increased from approximately 809 ha (2,000 acres)/year to 3,237 ha (8,000 acres)/ year, while maintaining average annual hectares of all other beneficial practices. Beginning in 2013, bird point count surveys were conducted annually to monitor northern bobwhite and grassland bird populations, including a subset of points under the National Bobwhite Conservation Initiative (NBCI) Coordinated Implementation Plan. To date, nearly 25,000 individual point counts have been performed in Texas (n = 20,111) and Oklahoma (n = 4,558). Working together, OPJV partners have made significant progress toward meeting grassland bird habitat and population objectives, while tracking progress and improving methods. However, there is still considerable work ahead.
Keywords: Oaks and Prairies Joint Venture; northern bobwhite; incentive program; habitat objective; OPJV; GRIP